Characteristics of lower limb surface electromyography in patients with knee osteoarthritis and progress in their exercise rehabilitation - SHAO Yunbo; GUO Jiayi; LI Feng; LI Jianqiang; YAO Kexin (Yixue xinzhi zazhi)
Knee osteoarthritis (KOA) is a common joint degenerative disease in clinical practice. The symptoms of lower limb muscle weakness, joint instability and other impaired motor function in long-term KOA patients can be captured by surface electromyography technology, and the representation form are mainly abnormal signals in the activation sequence, activation degree, coordinated movement pattern and fatigue pattern of lower limb muscles. Sports rehabilitation therapy is a necessary means to improve the lower limb motor function of KOA patients and reduce the recurrence rate of KOA. Using surface electromyography technology to expand the evaluation method of motor function can provide a scientific reference for KOA patients to develop long-term, targeted and efficient rehabilitation exercise therapy and muscle strength training, thereby further enriching the rehabilitation exercise methods of KOA. This article aims to reviewthe abnormal electro-physiological characterization of KOA patients' muscles and exercise rehabilitation programs, to enhance the guiding value of surface electromyography in the field of KOA exercise rehabilitation.